Inorganic compound crystal as well as preparation method and application thereof
By developing the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br, and preparing by hydrothermal crystallization method, the problems of insufficient second harmonic generation effect and insufficient thermal stability of existing nonlinear optical crystal materials are solved, and efficient second harmonic generation and excellent thermal stability are achieved, which are suitable for emerging optoelectronic technology fields.
Patent Information
- Application Number
- CN202411553811.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing nonlinear optical crystal materials have insufficient secondary harmonic effect under the action of strong laser light, and the thermal stability and optical characteristics need to be further improved to meet the needs of emerging optoelectronic technology fields.
A new inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br was developed, which was prepared by hydrothermal crystallization method, with strong second harmonic generation effect, and the powder frequency multiplication intensity was 9.8 times that of KH2PO4 (KDP), and phase matching can be achieved, with excellent thermal stability and high transmittance.
The inorganic compound crystal exhibits significant second harmonic generation effect under 1064nm laser irradiation, the frequency doubling intensity reaches 9.8 times that of KDP, and has good thermal stability and optical characteristics. It is suitable for emerging optoelectronic technology fields.
Smart Images

Figure CN119640403A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an inorganic compound crystal and a preparation method and application thereof, belonging to the field of inorganic materials. Background Art
[0002] Nonlinear optical crystals are a type of functional material widely used in the field of optoelectronic technology. Their unique nonlinear optical effects make them important in many fields such as laser processing, optical communication, and information storage. These crystals can produce nonlinear effects such as frequency doubling, sum frequency, and difference frequency under the action of strong lasers, thereby realizing the conversion of laser frequency. Through these frequency conversion processes, nonlinear optical crystals can convert infrared or visible light into light of other wavelengths, significantly broadening the application range of lasers.
[0003] At present, the nonlinear optical crystal materials in practical application include LiB3O5 (LBO), β-BaB2O4 (BBO), KH2PO4 (KDP), KTiOPO4 (KTP), α-AgIO3, AgGaS2 (AGS), ZnGeP2, etc. These materials are widely used in laser devices, optical fiber communications and quantum optics due to their strong nonlinear coefficients, stable physical properties and excellent optical properties. With the development of science and technology, the application prospects of nonlinear optical crystals in emerging fields such as optoelectronic devices and quantum communications are becoming more and more broad. Therefore, it is of great significance to develop new nonlinear optical crystals with excellent performance. Summary of the invention
[0004] According to the first aspect of the present application, an inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br is provided. The inorganic compound crystal exhibits a strong second harmonic generation effect, and its powder frequency-doubled intensity is 9.8 times that of KH2PO4(KDP) under 1064nm laser irradiation, and phase matching can be achieved, so it is a nonlinear optical material with potential application value.
[0005] An inorganic compound crystal, the chemical formula of which is Ga2(OH)(TeO3)(Te2O5)Br.
[0006] Optionally, in the crystal structure of the inorganic compound crystal, Ga(1)O6 and Ga(2)O6 octahedra are connected by sharing edges to form Ga2O 10 Dimers, these dimers are connected to each other through oxygen atoms to form a one-dimensional gallium oxide wavy chain along the c-axis;
[0007] The wavy gallium oxide chains are bridged by Te(1)O3 triangular pyramids to form two-dimensional gallium tellurite layers parallel to the bc plane;
[0008] The two-dimensional gallium tellurite layer is further connected through Te2O5 dimers to form a three-dimensional cation framework with Ga3Te3 hexavalent polyhedral annular channels along the b axis;
[0009] The isolated bromide anions are located in the six-membered polyhedral ring channel to balance the charge.
[0010] The crystal structure of the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br is as follows Figure 1 In this structure, Ga(1)O6 and Ga(2)O6 octahedra are connected by sharing edges to form Ga2O 10 Dimers, these dimers are connected to each other through oxygen atoms to form a one-dimensional gallium oxide wavy chain along the c-axis; the one-dimensional gallium oxide chain is bridged by Te(1)O3 triangular pyramids to form a two-dimensional gallium tellurite layer parallel to the bc plane; the two-dimensional gallium tellurite layer is further connected by Te2O5 dimers to form a three-dimensional cation framework with Ga3Te3 hexagonal polyhedral ring channels along the b-axis. The isolated bromine anion is located in the hexagonal polyhedral ring channels, forming the structure of Ga2(OH)(TeO3)(Te2O5)Br.
[0011] Optionally, the inorganic compound crystal belongs to the orthorhombic system, and the space group is Pca21;
[0012] Optionally, the unit cell parameters of the inorganic compound crystal are α=β=γ=90.000°, Z=4;
[0013] Preferably, the unit cell parameters are
[0014] Preferably, the unit cell parameters are
[0015] Specifically, the unit cell parameters are α=β=γ=90°, Z=4.
[0016] Optionally, the powder frequency-doubled intensity of the inorganic compound crystal under 1064 nm laser irradiation is 8 to 12 times that of KH2PO4 (KDP).
[0017] Optionally, the powder frequency-doubled intensity of the inorganic compound crystal under 1064 nm laser irradiation is 9 to 11 times that of KH2PO4 (KDP).
[0018] Optionally, the powder frequency-doubled intensity of the inorganic compound crystal under 1064 nm laser irradiation is 9.8 times that of KH2PO4 (KDP).
[0019] Optionally, the ultraviolet absorption cutoff wavelength of the inorganic compound crystal is 270-310 nm.
[0020] Optionally, the ultraviolet absorption cutoff wavelength of the inorganic compound crystal is 280-310 nm.
[0021] Optionally, the ultraviolet absorption cutoff wavelength of the inorganic compound crystal is 289 nm.
[0022] Optionally, the inorganic compound crystals lose weight by no more than 5% at 420°C.
[0023] Optionally, the inorganic compound crystals lose weight by no more than 3% at 420° C., and their physical phase does not change.
[0024] That is, the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br can be stable to 420℃.
[0025] According to the second aspect of the present application, a method for preparing the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br described above is provided. The preparation method adopts a hydrothermal crystallization method, and the preparation process is simple, and a high-purity, high-crystallinity inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br material can be obtained.
[0026] A raw material mixture containing gallium, tellurium, bromine and water is placed in a sealed container and crystallized to obtain the inorganic compound crystal.
[0027] Optionally, in the raw material mixture, the molar ratio of gallium, tellurium, bromine and water is:
[0028] Ga: Te: Br: H2O=1~4: 0.5~4.5: 0.1~2.0: 10~300.
[0029] Optionally, in the raw material mixture, the molar ratio of gallium, tellurium, bromine, bismuth and water is:
[0030] Ga: Te: Br: H2O=1.3~3.5: 0.8~4.0: 0.5~1.8: 30~200.
[0031] Optionally, in the raw material mixture, the molar ratio of gallium, tellurium, bromine, bismuth and water is:
[0032] Ga: Te: Br: H2O=1.5~3.2: 1.0~3.5: 0.8~1.5: 50~100.
[0033] Optionally, the raw material mixture further includes bismuth element;
[0034] The molar ratio of the gallium element to the bismuth element is: Ga:Bi=1-4:0.1-3.
[0035] Optionally, the molar ratio of the gallium element to the bismuth element is: Ga:Bi=1.3~3.5:0.2~2.
[0036] Preferably, the molar ratio of the gallium element to the bismuth element is: Ga:Bi=1.5-3.2:0.3-1.
[0037] Optionally, in the raw material mixture, the gallium element comes from at least one of gallium oxide, gallium chloride, gallium nitrate, and gallium bromide; the tellurium element comes from at least one of tellurium dioxide, sodium tellurite, potassium tellurite, and telluric acid; and the bromine element comes from at least one of sodium bromide, bismuth bromide, potassium bromide, hydrobromic acid, cesium bromide, calcium bromide, cuprous bromide, lead bromide, lithium bromide, stannous bromide, and silver bromide.
[0038] Optionally, the bismuth element is at least one of bismuth bromide, bismuth chloride, bismuth oxide and bismuth nitrate. The bismuth element is used as an auxiliary agent.
[0039] Preferably, in the raw material mixture, the gallium element comes from gallium trioxide; the tellurium element comes from tellurium dioxide; the bromine element comes from hydrobromic acid; and the bismuth element comes from bismuth bromide.
[0040] Optionally, the hydrobromic acid is an aqueous solution of hydrogen bromide with a concentration of 40 wt% to 100 wt%.
[0041] Optionally, the crystallization temperature is 150° C. to 300° C., and the crystallization time is 24 hours to 200 hours.
[0042] Preferably, the crystallization temperature is 180° C. to 280° C., and the crystallization time is 50 hours to 170 hours.
[0043] Preferably, the crystallization temperature is 190° C. to 270° C., and the crystallization time is 72 hours to 150 hours.
[0044] Optionally, the upper limit of the crystallization temperature is selected from 300℃, 290℃, 280℃, 270℃, 260℃, 250℃, 240℃, 230℃, 220℃, 210℃, 200℃, 190℃, 180℃, 170℃ or 160℃; the lower limit is selected from 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃ or 290℃.
[0045] Optionally, the upper limit of the crystallization time is selected from 200h, 190h, 180h, 170h, 150h, 120h, 110h, 100h, 96h, 80h, 72h, 70h, 60h, 50h, 48h, 36h or 30h; the lower limit is selected from 24h, 30h, 36h, 48h, 50h, 60h, 70h, 72h, 80h, 96h, 100h, 110h, 120h, 150h, 170h, 180h or 190h.
[0046] Optionally, after the crystallization is completed, the temperature is lowered to room temperature, and the inorganic compound crystals are obtained after separation and drying;
[0047] Optionally, the cooling rate is 0.5 to 15°C / h.
[0048] Preferably, the cooling rate is 2-12°C / h.
[0049] Optionally, the upper limit of the cooling rate is selected from 15℃ / h, 13℃ / h, 12℃ / h, 10℃ / h, 8℃ / h, 6℃ / h, 4℃ / h, 3℃ / h, 2℃ / h or 1℃ / h; the lower limit is selected from 0.5℃ / h, 1℃ / h, 2℃ / h, 3℃ / h, 4℃ / h, 6℃ / h, 8℃ / h, 10℃ / h, 12℃ / h or 13℃ / h.
[0050] As a preferred embodiment, the method for preparing the inorganic compound crystal comprises the following steps:
[0051] (a) placing a raw material mixture containing gallium, tellurium, bromine, bismuth and water in a reaction vessel lined with polytetrafluoroethylene, sealing the reaction vessel and crystallizing the reaction vessel at a crystallization temperature of 180 to 300° C. for more than 24 hours;
[0052] (b) After the crystallization is completed, the system is cooled to room temperature at a cooling rate not exceeding 15° C. / h. The solid sample obtained after separation and drying is the inorganic compound crystal.
[0053] The inorganic compound crystals prepared by the hydrothermal method have the morphology of colorless and transparent rod-shaped crystals.
[0054] According to the third aspect of the present application, there is provided an application of the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br as a nonlinear optical crystal material.
[0055] According to a fourth aspect of the present application, there is provided an application of the above-mentioned inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br in an optical device.
[0056] In this application, "room temperature" refers to 25°C.
[0057] The beneficial effects of this application include:
[0058] 1) The inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br provided in the present application. The inorganic compound crystal exhibits a strong second harmonic generation effect. Under 1064nm laser irradiation, its powder frequency-doubled intensity is 9.8 times that of KH2PO4(KDP), and phase matching can be achieved, which is a nonlinear optical material with potential application value.
[0059] 2) The inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br provided in the present application has a very high transmittance in the spectral range of 289-1500nm, and its ultraviolet absorption cut-off wavelength is about 289nm.
[0060] 3) The inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br provided in the present application can be stabilized to 420°C and has excellent thermal stability.
[0061] 4) The preparation method of the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br provided in the present application adopts a hydrothermal crystallization method to grow a colorless rod-shaped Ga2(OH)(TeO3)(Te2O5)Br crystal. The method is simple in process and can obtain a high-purity, high-crystallinity inorganic compound Ga2(OH)(TeO3)(Te2O5)Br crystal material. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a schematic diagram of the crystal structure of the inorganic compound Ga2(OH)(TeO3)(Te2O5)Br, where: Figure 1 (a) is a one-dimensional gallium-oxygen chain; Figure 1 (b) is a two-dimensional gallium tellurite layer; Figure 1 (c) is the crystal structure of the compound.
[0063] Figure 2 It is sample 1 # The X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after the sample is ground into powder.
[0064] Figure 3 It is sample 1 # The frequency harmonic intensity and phase matching diagram.
[0065] Figure 4 It is sample 1 # UV-Vis-NIR diffuse reflectance spectrum.
[0066] Figure 5 It is sample 1 # Thermogravimetric diagram of . DETAILED DESCRIPTION
[0067] The present application is described in detail below in conjunction with the examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials and reagents used in the present application are purchased from commercial sources and used directly without treatment, and the instruments and equipment used adopt the schemes and parameters recommended by the manufacturers.
[0068] Example 1 Hydrothermal Synthesis of Samples
[0069] The raw materials are prepared according to a certain molar ratio, placed in a polytetrafluoroethylene-lined reactor, and then heated to the crystallization temperature. After being kept constant at this temperature for a period of time, the system temperature is lowered to room temperature at a certain cooling rate. After suction filtration and washing, a colorless rod-shaped crystal sample is obtained, which is the sample of the inorganic compound crystal.
[0070] The sample number, raw material type and amount, crystallization temperature and holding time, and cooling rate are shown in Table 1. Among them, HBr comes from a 40wt% HBr aqueous solution, and the molar ratio refers to the molar ratio of gallium, tellurium, bromine, bismuth, and water in the raw material mixture.
[0071] Table 1
[0072]
[0073]
[0074] Example 2 Crystal structure analysis
[0075] The single crystal X-ray diffraction and powder X-ray diffraction methods were used to analyze the # ~4 # Perform structural analysis.
[0076] The single crystal X-ray diffraction was performed on a SuperNova CCD X-ray single crystal diffractometer from Agilent, USA. The data collection temperature was 298K, the diffraction light source was graphite monochromatized Mo-Kα ray scanning mode was ω-2θ; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 1.5 program package; the position of heavy atoms was determined by the direct method, and the coordinates of the remaining atoms were obtained by the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.
[0077] Powder X-ray diffraction was carried out on a Miniflex 600 X-ray powder diffractometer from RIGAKU Co., Ltd., Japan. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength of The voltage and current were 30 kV / 15 A, the scanning range was 10-70°, and the scanning step was 0.02°.
[0078] Among them, the single crystal X-ray diffraction results show that sample 1 # ~4 # The chemical formula is Ga2(OH)(TeO3)(Te2O5)Br, belonging to the orthorhombic system, the space group is Pca21, the unit cell parameters α=β=γ=90.000°, Z=4. The crystal structure of the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br is as follows Figure 1 In this structure, Ga(1)O6 and Ga(2)O6 octahedra are connected by sharing edges to form Ga2O 10 These dimers are connected to each other through oxygen atoms to form a one-dimensional wavy gallium oxide chain along the c-axis; the gallium oxide chain is bridged by Te(1)O3 triangular pyramids to form a two-dimensional gallium tellurite layer parallel to the bc plane; the two-dimensional gallium tellurite layer is further connected by Te2O5 dimers to form a three-dimensional cation framework with Ga3Te3 hexagonal polyhedral ring channels along the b-axis; the isolated bromine anion is located in the hexagonal polyhedral channel, forming the structure of Ga2(OH)(TeO3)(Te2O5)Br ( Figure 1 ).
[0079] Take sample 1 # It is a typical representative, belonging to the orthorhombic system, with a space group of Pca21 and a unit cell parameter of α=β=γ=90°, Z=4.
[0080] The powder X-ray diffraction results showed that sample 1 # ~4 # In the XRD spectrum, the peak positions are basically the same, but the peak intensities of each sample are slightly different.
[0081] Take sample 1 # As a typical representative, Figure 2 As shown in Figure 1, according to the crystal structure analyzed by single crystal X-ray diffraction, the fitted X-ray diffraction pattern is consistent with that of sample 1. # After grinding into powder, the peak positions and peak intensities of the X-ray diffraction test were consistent, indicating that the samples obtained were of high purity.
[0082] Example 3 Frequency doubling test experiment and results
[0083] Take sample 1 #As a representative example, the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br was subjected to frequency doubling test.
[0084] The specific steps are as follows: Use a laser with a wavelength of 1064nm as the fundamental frequency light to irradiate the crystal powder to be tested, use a photomultiplier tube to detect the generated second harmonic, and use an oscilloscope to display the harmonic intensity. Use a standard sieve to sieve out crystals of different particle sizes from the crystal sample to be tested, and the particle sizes are 45-53μm, 53-75μm, 75-105μm, 105-150μm, 150-210μm, and 210-300μm. Observe the change trend of the double-frequency signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, compare the intensity of the second harmonic generated by the sample to be tested with the second harmonic intensity generated by the reference crystal KH2PO4 (KDP), so as to obtain the relative size of the sample double-frequency effect.
[0085] The test results are as follows Figure 3 As shown: The second harmonic generation intensity of the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br measured at 1064nm is 9.8 times that of KH2PO4(KDP), and phase matching can be achieved.
[0086] Example 4 Diffuse reflection absorption spectrum test
[0087] Take sample 1 # As a representative, the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br was tested by diffuse reflectance absorption spectroscopy on a Lambda-950 UV-visible-near infrared spectrophotometer from Perkin-Elmer, USA. The crystal sample was ground into powder and BaSO4 was used as a reference substrate. The test results are shown in Figure 2. Figure 4 As shown, the crystal of the compound Ga2(OH)(TeO3)(Te2O5)Br has a wide transmittance range, a very high transmittance in the spectral range of 289-1500nm, and an ultraviolet absorption cut-off wavelength of about 289nm.
[0088] Thermogravimetric analysis of samples of Example 5
[0089] Take sample 1 # As a representative example, the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br was subjected to thermogravimetric analysis on a STA449F3 thermogravimetric analyzer from NETZSCH, Germany. The results are as follows: Figure 5 As shown in the figure, it can be seen that Ga2(OH)(TeO3)(Te2O5)Br crystals can be stable to 420℃.
[0090] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. An inorganic compound crystal, characterized in that: The chemical formula of the inorganic compound crystal is Ga2(OH)(TeO3)(Te2O5)Br.
2. The inorganic compound crystal according to claim 1, characterized in that: In the crystal structure of the inorganic compound crystal, Ga(1)O6 and Ga(2)O6 octahedra are connected by sharing edges to form Ga2O 10 Dimers, these dimers are connected to each other through oxygen atoms to form a one-dimensional wavy gallium oxide chain along the c-axis; The gallium oxide chains are bridged by Te(1)O3 triangular pyramids to form a two-dimensional gallium tellurite layer parallel to the bc plane; The two-dimensional gallium tellurite layer is further connected by Te2O5 dimers to form a three-dimensional cationic framework with Ga3Te3 hexavalent polyhedral ring channels along the b axis; Isolated bromide anions are located in the six-membered polyhedral channels to balance the charge.
3. The inorganic compound crystal according to claim 1, characterized in that: The inorganic compound crystal belongs to the orthorhombic system and the space group is Pca21; Preferably, the unit cell parameters of the inorganic compound crystal are α=β=γ=90.000°, Z=4; Preferably, the unit cell parameters are Preferably, the unit cell parameters are 4. The inorganic compound crystal according to claim 1, characterized in that: The intensity of the powder double frequency of the inorganic compound crystal measured under 1064nm laser is 8 to 12 times that of KH2PO4; Preferably, the ultraviolet absorption cutoff wavelength of the inorganic compound crystal is 270 to 310 nm; Preferably, the inorganic compound crystals lose no more than 5% of their weight at 420°C.
5. The method for preparing an inorganic compound crystal according to any one of claims 1 to 4, characterized in that: A raw material mixture containing gallium, tellurium, bromine and water is placed in a sealed container and crystallized to obtain the inorganic compound crystal.
6. The preparation method according to claim 5, characterized in that: In the raw material mixture, the molar ratio of gallium, tellurium, bromine and water is: Ga: Te: Br: H2O=1~4: 0.5~4.5: 0.1~2.0: 10~300; Preferably, in the raw material mixture, the molar ratio of gallium, tellurium, bromine and water is: Ga: Te: Br: H2O=1.3~3.5: 0.8~4.0: 0.5~1.8: 30~200; Preferably, in the raw material mixture, the molar ratio of gallium, tellurium, bromine and water is: Ga: Te: Br: H2O=1.5~3.2: 1.0~3.5: 0.8~1.5: 50~100; Preferably, the raw material mixture further includes bismuth element; The molar ratio of the gallium element to the bismuth element is: Ga:Bi=1-4:0.1-3; Preferably, the molar ratio of the gallium element to the bismuth element is: Ga:Bi=1.3-3.5:0.2-2; Preferably, the molar ratio of the gallium element to the bismuth element is: Ga:Bi=1.5-3.2:0.3-1.
7. The preparation method according to claim 5 or 6, characterized in that: In the raw material mixture, the gallium element comes from at least one of gallium oxide, gallium chloride, gallium nitrate, and gallium bromide; the tellurium element comes from at least one of tellurium dioxide, sodium tellurite, potassium tellurite, and telluric acid; the bromine element comes from at least one of sodium bromide, bismuth bromide, potassium bromide, hydrobromic acid, cesium bromide, calcium bromide, cuprous bromide, lead bromide, lithium bromide, stannous bromide, and silver bromide; Preferably, the bismuth element comes from at least one of bismuth bromide, bismuth chloride, bismuth oxide and bismuth nitrate.
8. The preparation method according to claim 5, characterized in that: The crystallization temperature is 150°C to 300°C, and the crystallization time is 24 hours to 200 hours; Preferably, the crystallization temperature is 180°C to 280°C, and the crystallization time is 50 hours to 170 hours; Preferably, the crystallization temperature is 190° C. to 270° C., and the crystallization time is 72 hours to 150 hours; Preferably, after the crystallization is completed, the temperature is lowered to room temperature, and the inorganic compound crystals are obtained after separation and drying; Preferably, the cooling rate is 0.5 to 15°C / h; Preferably, the cooling rate is 2-12°C / h.
9. Use of the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br as claimed in any one of claims 1 to 4 as a nonlinear optical crystal material.
10. Use of the inorganic compound crystal Ga2(OH)(TeO3)(Te2O5)Br according to any one of claims 1 to 4 in optical devices.
Citation Information
Patent Citations
Inorganic compound crystal, preparation method and application thereof
CN107841786A
Inorganic compound crystal as well as preparation method and application thereof
CN113802182A
Inorganic compound crystal as well as preparation method and application thereof
CN114197050A